2017
DOI: 10.1016/j.bbamcr.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 6-dependent sestrin 2 induction ameliorates ER stress-mediated liver injury

Abstract: Endoplasmic reticulum (ER) stress is characterized by an accumulation of misfolded proteins, and ER stress reduction is essential for maintaining tissue homeostasis. However, the molecular mechanisms that protect cells from ER stress are not completely understood. The present study investigated the role of sestrin 2 (SESN2) on ER stress and sought to elucidate the mechanism responsible for the hepatoprotective effect of SESN2 in vitro and in vivo. Treatment with tunicamycin (Tm) increased SESN2 protein and mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Conversely, if Sesn2 is lacking, cells are highly susceptible to ER stress-associated cell death due to the continued translation of large amounts of protein [14]. A recent study indicated that the induction of Sesn2 under ER stress is dependent on activating transcription factor 6, and Sesn2 plays a hepatoprotective role in the presence of excess ER stress by inhibiting CCAAT-enhancer-binding protein homologous protein, c-Jun N-terminal kinase (JNK), and p38 [40]. ER stress is an aspect of the pathogenesis of aging and a variety of human diseases, such as cardiovascular diseases; however, the transcription factors involved in the induction of Sesn2 by ER stress and the protective mechanisms triggered by Sesn2 against ER stressmediated cell death require further exploration.…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…Conversely, if Sesn2 is lacking, cells are highly susceptible to ER stress-associated cell death due to the continued translation of large amounts of protein [14]. A recent study indicated that the induction of Sesn2 under ER stress is dependent on activating transcription factor 6, and Sesn2 plays a hepatoprotective role in the presence of excess ER stress by inhibiting CCAAT-enhancer-binding protein homologous protein, c-Jun N-terminal kinase (JNK), and p38 [40]. ER stress is an aspect of the pathogenesis of aging and a variety of human diseases, such as cardiovascular diseases; however, the transcription factors involved in the induction of Sesn2 by ER stress and the protective mechanisms triggered by Sesn2 against ER stressmediated cell death require further exploration.…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…It was originally found that the expression of sestrin1 and sestrin2 was regulated by p53 [6], whereas the expression of sestrin3 was regulated by transcription factor forkhead box O (FOXO) [21,22]. Later, additional studies reveal several regulators crucial for the expression of sestrins under various stressful conditions; these include nuclear factor erythroid 2 like 2 (Nrf2), activating transcription factor4 (ATF4), ATF6, c-Jun N-terminal kinase (JNK)/c-Jun pathway, hypoxia-inducible factor-1α (HIF-1α), X-box-binding protein 1 (XBP1), and CCAAT/enhancer-binding protein beta (C/EBPβ) [23,24,25,26,27,28]. Together, these previous reports imply vital roles of sestrins in coping with cellular stress under different physiological and pathological conditions.…”
Section: Sestrins: An Acute Stress-responsive Proteinmentioning
confidence: 99%
“…It was reported that SESNs protected cells against various stimuli by regulating autophagy, ERS, metabolism, and apoptosis. As the unique protein in SESNs family, SESN2 was found to be upregulated by the activation of ERS signaling pathways and be an important protective factor on relieving cell injury and cell death [19][20][21][22][23][24] . We proposed that SESN2 might be one of the favorable factors in immune regulation of DCs under ERS in the setting of sepsis.…”
Section: Introductionmentioning
confidence: 99%